KONTEN KREATIF MEDIA SOSIAL TERHADAP MINAT PELANGGAN BOOTSTRAP SHOESCARE - Basrahil, Rahel (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This study aims to analyze the influence of creative social media content on customer interest in using the services of Bootstrap Shoescare, a micro, small, and medium enterprise (MSME) specializing in shoe care services in Banjarbaru. The background of this research lies in the growing dominance of platforms such as Instagram in MSME marketing and the need for Bootstrap Shoescare to build customer attention, interaction, and trust. The research employed a quantitative approach with an explanatory design. A total of 100 respondents were selected using purposive sampling (criteria: active social media users residing in Banjarbaru who have used or are potential users of the service). The instrument was a four-point Likert scale questionnaire developed based on indicators of creative content (educational value, visual appeal, interactivity, and authentic testimonials) and guided by the AIDA and TPB theories. Data analysis included validity and reliability testing, simple linear regression, Pearson correlation, and t-test using SPSS software. The results indicate that creative social media content has a positive and significant effect on customer interest. The coefficient of determination (R² ? 0.532) suggests that approximately 53.2% of the variance in customer interest is explained by the creative content variable. The practical implication highlights the importance of focusing on educational content, before–after visuals, interactivity, and authentic testimonials to increase customer conversion.   Keywords: Creative Content, Social Media, Customer Interest, Bootstrap Shoescare, Instagram.